A novel variable geometry turbine achieved by elastically restrained nozzle guide vanes. Part II: Experimental evaluation. (July 2022) - Wang, Zhihui; Ma, Chaochen; Liyong, Huang
The current paper presents the performance results of a variable-flow turbocharger turbine, called the "elastically restrained guide vane (ERGV)" turbine, which is intended to provide an improvement over the current state-of-the-art turbochargers, namely, the variable geometry turbocharger (VGT). This paper is a continuation of the previous work and concentrates on the experimental testing of the ERGV turbine performance, as well as the corresponding effects on the mass flow characteristic as a result of operating the turbocharger in its ERGV mode compared with its operation as a traditional VGT. The effects of the ERGV application are demonstrated through the first experimental testing. In this preliminary attempt, the range of the mass flow rate is effectively enlarged, and the new mass flow characteristic lines can pass through the two and three lines separately of the original turbine for the two spring stiffness operations. The results of this study were encouraging with respect to the potential of ERGV to replace the traditional VGT in particular applications. Additionally, this paper compares the experimental mass flow charateristics with the computational fluid dynamics simulations in the radial turbine at the conditions of two spring stiffness. This preliminary comparison between numerical simulation and experimental data shows encouraging results.